Rethinking Communication and Interaction. Challenges and Opportunities in Times of Crisis. Book of Abstracts - IANCU, Ioana; CULIC, Lorina; PAVELEA, Anișoara (2022)
Being already a tradition, the International Student’s Conference on Communication,organized by the Department of Communication, Public Relations and Advertising, Faculty ofPolitical, Administrative and Communication Sciences, Babeș-Bolyai University, Cluj-Napoca, iscelebrating its ninth edition (19 May 2021). The conference is developed in collaboration with theCommunication and Social Innovation Research Center (CORE). Each year, the conference offersthe bachelor, master and doctoral students the opportunity to share their research interests and theirfascinating empirical results, to exchange ideas and feedback on their work, and to develop criticalskills of analysis and presentation.Considering the pandemic context, the topic of the conference is Rethinking Communicationand Interaction. Challenges and Opportunities in Times of Crisis. The present volume is a book ofextended abstracts, enjoying the participation of 46 topics. The volume has six major chapters, out ofwhich one is dedicated to the doctoral students.